PELAKSANAAN KEGIATAN RATIBUL HADDAD BAGI NARAPIDANA NARKOTIKA DILEMBAGA PEMASYARAKATAN KELAS II A JEMBER - Farichah, Siti Dawiyah; Maiysharatul K, Siti (EL-Islam, 2024)
The objectives of this research are: 1) Describe how Ratibul Haddad activities are implemented for narcotics prisoners at the Jember Class II A Penitentiary. 2) To find out what supporting and inhibiting factors are the implementation of Ratibul Haddad activities for narcotics prisoners at the Jember Class II A Penitentiary. 3) To find out what impact the implementation of Ratibul Haddad activities has on narcotics prisoners at the Jember Class II A Correctional Institution. Researchers use a qualitative research approach with a phenomenological type. The description of the form of implementation of the Ratibul Haddad activity is the same as Istigosahin general, which begins with preparing the place first and preparing mats, the Ratibul Haddad reading text for those who don't memorize it and the tools that will be used for the activity such as loudspeakers if needed. Next, the activity begins with tawasul fatihah, prayers, reading Ratibul Haddad and ends with prayer. The inhibiting and supporting factors for implementing RatibulHaddad activities are the prisoners themselves who are difficult to invite to carry out coaching activities. The effect of implementing Ratibul Haddad activities for narcotics prisoners is that they make their hearts calmer and more peaceful, increase their sense of responsibility, and have high social awareness.